2003
DOI: 10.1177/0146167202238376
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Trait Typicality in Gender Stereotypes: Examining the Role of Attribution and Categorization Processes

Abstract: Gender stereotypes are understood as the ascription of different personality traits to men and women. Data from American and Italian samples showed that consistent with the attribution hypothesis, the estimated prevalence of a trait in a target group predicted perceptions of trait typicality well. In contrast, there was no support for the categorization hypothesis, according to which perceived differences in trait prevalence between groups should independently predict trait typicality. Nevertheless, participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
1
21
0
2
Order By: Relevance
“…A rich literature demonstrates that idealized leadership traits are frequently gendered as male. A short list includes Aalberg and Jenssen 2007;Alexander and Andersen 1993;Fullagar et al 2003;Huddy and Terkildsen 1993;Krueger et al 2003;Lawless 2004;and Sanbonmatsu 2002. some cultural contexts, advantage male candidates. In other cultural contexts, however, I expect the personal vote to have no effect on women's legislative representation, and in still others, it could conceivably benefit female candidates; the effect of this institution depends on how voters use the "information" of gender when they are faced with a female candidate.…”
Section: The Effect Of the Personal Vote On Women's Legislative Reprementioning
confidence: 99%
“…A rich literature demonstrates that idealized leadership traits are frequently gendered as male. A short list includes Aalberg and Jenssen 2007;Alexander and Andersen 1993;Fullagar et al 2003;Huddy and Terkildsen 1993;Krueger et al 2003;Lawless 2004;and Sanbonmatsu 2002. some cultural contexts, advantage male candidates. In other cultural contexts, however, I expect the personal vote to have no effect on women's legislative representation, and in still others, it could conceivably benefit female candidates; the effect of this institution depends on how voters use the "information" of gender when they are faced with a female candidate.…”
Section: The Effect Of the Personal Vote On Women's Legislative Reprementioning
confidence: 99%
“…In the area of stereotype research, the study of gender stereotypes has held a prominent place; it is one of the most common and most studied group stereotypes (e.g., Diekman and Eagly 2000;Krueger et al 2003). Gender stereotypes are pervasive, widely shared, and have proved to be resistant to change (e.g., Heilman 2001).…”
Section: How Negative Campaigning Influences Views Of Men and Women Cmentioning
confidence: 99%
“…Several early studies revealed that gender stereotypes were consistently maintained and exceedingly conventional (Fernberger, 1948; Kirkpatrick, 1936; Sheriffs & McKee, 1957). Half a century later, findings suggest that gender stereotypes still are prevalent (e.g., Krueger, Hasman, Acevedo, & Villano, 2003; Sczesny, Spreemann, & Stahlberg, 2006). Gender stereotypes may extend virtually to all aspects of human life, from personality traits to occupations, and possibly even to body image and eating behaviors.…”
mentioning
confidence: 99%